2016
DOI: 10.1002/2016gc006295
|View full text |Cite
|
Sign up to set email alerts
|

Experimental constraints on the serpentinization rate of fore‐arc peridotites: Implications for the upwelling condition of the slab‐derived fluid

Abstract: To constrain the water circulation in subduction zones, the hydration rates of peridotites were investigated experimentally in fore‐arc mantle conditions. Experiments were conducted at 400–580°C and 1.3 and 1.8 GPa, where antigorite is expected to form as a stable serpentine phase. Crushed powders of olivine ± orthopyroxene and orthopyroxene + clinopyroxene were reacted with 15 wt % distilled water for 4–19 days. The synthesized serpentine varieties were lizardite and aluminous lizardite (Al‐lizardite) in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 74 publications
2
29
0
Order By: Relevance
“…High V P /V S ratios observed in mantle wedges within subduction zone environments were interpreted on the basis of serpentine elastic properties (Christensen, 1996). Antigorite is an abundant hydrous mineral in subduction zones and contributes to the transportation of water into the mantle, influences slab-mantle coupling, the distribution of slab earthquakes, and triggers partial melting of lithospheric upper mantle (Bostock et al, 2002;Nakatani & Nakamura, 2016;Rüpke et al, 2004;Ulmer & Trommsdorff, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…High V P /V S ratios observed in mantle wedges within subduction zone environments were interpreted on the basis of serpentine elastic properties (Christensen, 1996). Antigorite is an abundant hydrous mineral in subduction zones and contributes to the transportation of water into the mantle, influences slab-mantle coupling, the distribution of slab earthquakes, and triggers partial melting of lithospheric upper mantle (Bostock et al, 2002;Nakatani & Nakamura, 2016;Rüpke et al, 2004;Ulmer & Trommsdorff, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The starting material was a powdered mixture of olivine and Opx handpicked separately from a gently crushed San Carlos lherzolite xenolith. The chemical compositions of olivine and Opx have been reported previously (Nakatani & Nakamura, ). The olivine and Opx have X Mg (=Mg/(Mg + Fe) in molar ratio) values of 0.91, and Opx is characterized by a high Al 2 O 3 content (4.07 wt%).…”
Section: Methodsmentioning
confidence: 63%
“…It is difficult to classify this serpentine variety unambiguously based on the Raman spectrum because the OH‐stretching band, which is decisive for discriminating serpentine varieties, is broad possibly owing to the low crystallinity of the synthesized serpentine. A serpentine variety with similar mineralogical characters was synthesized by Nakatani and Nakamura () at 400–580 °C and 1.3 GPa and was regarded as lizardite. They suggested that high aluminum activity in the system stabilized lizardite even in the high P ‐ T conditions, where antigorite is stable in the less Al 2 O 3 ‐rich system (Caruso & Chernosky, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations